Quantitative analysis of qualitative data: Using voyant tools to investigate the sales-marketing interface - Gabor Hetenyi; Attila Lengyel; Magdolna Szilasi (Journal of Industrial Engineering and Management (JIEM), 2019)
Purpose: The present study aims to give a short introduction into the possibilities offered by Voyant Tools to quantitatively explore qualitative data on the Sales-Marketing Interface (SMI). Design/methodology/approach: The study is exploratory in nature. The sample consists of sales and marketing employees of six manufacturing companies. Answers to three open-ended questions were analysed quantitatively and visualised in various ways using the online toolset of Voyant Tools. We experimented with four different tools out of the twenty four offered by Voyant Tools. These tools were: Cyrrus tool, Correlation tool, Topics tool and Scatter plot tool. All four tools that were tested on the data have scalable parameters. Various settings were tested to demonstrate how input conditions influence modelling of the textual data. Findings: It was demonstrated that the four selected text analysis tools can yield valuable information depicted in the form of attractive visualisation formats. It is also highlighted how rushed conclusions can be arrived at by falsely interpreting the visualised data. It is shown how setting different input parameters can affect results. Out of the four examined tools the Scatter plot tool offering an analysis and modelling method based on t-SNE (t-Distributed Stochastic Neighbour Embedding) proved to yield the most complex information about the text. Research limitations/implications: As the study aimed to be exploratory a sample of convenience was used to collect qualitative data. Although quantitative methods can be invaluable tools of preliminary analysis and hypothesis adjustment in the processing of qualitative data, their results should always be checked against the traditional content analysis techniques which are more sensitive to the complex structure of semantic units. These quantitative techniques are to help early exploration of textual data. Practical implications: Managerial implications might be connected to the fact that in a fast changing global business environment managers and corporate decision makers in general might find the attractive visualisation outputs of Voyant Tool easy to analyse and interprete various aspects of business. As Voyant Tools is an open source, free online sofware not even requiring regsitration and at the same time has an impressive array of sophisticated statistical tools, it might be a cost-effective way of analysing qualitative data. Originality/value: As there is virtually no earlier literature on how quantitative data visualisation techniques can be used in marketing research, especially in the analysis of the SMI, utilisation possibilities of Voyant Tools and other quantitative data analysis and visualisation software for handling qualitative data is definitely a worthwhile area for further research.
Keywords: 650; qualitative research; qualitative data visualisation; qualitative marketing research; Voyant Tools; Sales-Marketing Interface